Enhancing Students’ English Vocabulary Through The Use Of Storyjumper In Efl Classroom - Rahmawati Upa; Sri Rahayu; Hermini Hermini (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Vocabulary mastery is one of crucial component of language proficiency which directly influence students’ ability in speaking, reading, listening, and writing. However, many EFL students struggle with vocabulary acquisition due to limited exposure, lack of contextual learning, and low engagement. This research aimed to examine the effectiveness of StoryJumper, a digital storyteling platform, in enhancing English vocabulary among eighth grade students in one of Junior high school in Palopo. This research involved 31 students and adopted a pre-experimental one group pre-test and post-test design. During the intervention, students created and narrated their own digital stories using StoryJumper, which encouraged them to use target vocabulary in meaningful context, collaborate with peers, and repeatedly encounter the words in both receptive and productive modes. Data were collected through vocabulary tests administered before and after the treatment. Descriptive statistics showed an increase in the mean score from 58.71 in the pre-test to 76.13 in the post-test, and a paired sample t-test confirmed that the improvement was statistically significant. The findings indicate that StoryJumper not only improved students vocabulary retention but also increased their motivation and engagement in learning. The positive impact is attributed to contextualized learning, repeated exposure, peer collaboration, and the multimodal nature of digital storytelling. This research recommends the future researchers to explore the long term impact of StoryJumper on other language skills such as writing or speaking. In addition, a comparison with other storytelling tools or control groups may yield deeper insights into its effectiveness